Farmers and village life in twentieth-century Japan - Waswo, Ann; Nishida, Yoshiaki, 1940-2012 (RoutledgeCurzon, 2003)
Rural Japan during the twentieth century has been portrayed as a vast reservoir of conservatism in much of the literature on Japan's modern development, and Japanese agriculture since the 1960s has been treated as an artificial creation sustained only by protectionism of the worst sort. This book presents a range of original, in-depth work, including work by Japanese scholars, that seeks to move beyond such stereotypes to reveal the diversity and complexities of rural life in Japan from 1900 to the present.